Hallucinating Gonçalo M. Tavares’ "Short Movies" - Eiras, Pedro (2020)
Short Movies, by the Portuguese author Gonçalo M. Tavares (2011), is hard to define in the field of literary or artistic genres. There are no movies in this book, just verbal descriptions of possible movies, usually marked by intense violence; but these descriptions, in turn, resemble to cinematic scripts, suggesting a set of shots, camera movements, the grammar of a montage. In this hybrid way of writing, the film is an object that remains both present and absent, continually summoned and always deferred. What operation is then required of the reader of this book, what gesture between reading and seeing, what theory of epistemology, what kind of controlled hallucination? In short, this essay proposes that Short Movies invites to the development of a subtle and painful art of suspicion.